GBTX emulator for development and special versions of GBT-based readout chains. (17th December 2021) - Zabołotny, W.M.; Byszuk, A.P.; Dementev, D.; Emschermann, D.; Gumiński, M.; Kruszewski, M.; Miedzik, P.; Poźniak, K.; Romaniuk, R.; Schmidt, C.J.; Shitenkov, M.
Abstract: The GBTX ASIC is a standard solution for providing fast control and data readout for radiation detectors used in HEP experiments. However, it is subject to export control restrictions due to the usage of radiation-hard technology. An FPGA-based GBTX emulator (GBTxEMU) has been developed to enable the development of GBT-based readout chains in countries where the original GBTX cannot be imported. Thanks to utilizing a slightly modified GBT-FGPA core, it maintains basic compatibility with standard GBT-based systems. The GBTxEMU also may be an interesting solution for developing GBT-based readout chains for less demanding experiments.